PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENGENDALIAN DAN PENILAIAN KINERJA MANAJER PRODUKSI (STUDI KASUS PADA PABRIK PUTRI PANDA) - PUTU ADNYANI, NILUH (Jurnal Akuntansi AKUNESA, 2015)
Abstract: This researchs aimed to know how the controlling and assessing performance of Putri Panda factory production manager using responsibility accounting system. Method used in this research is case study with descriptive qualiative analysis. Data source is primary which is interview with involved informant, and secondary as a compliment. Result of this research showed that Putri Panda factory has well implemented responsibility accounting system. That means it has an organization structure with good dividing between right and responsibilitty. Budgeting involves active participation from all entire production department. There is a cost classification, related to separation between controlled and uncontrolled cost. But there is no account numbering based on management levels. The cost reporting is good. Variance analysis result showed good performance of production manager. However there are some results that “unfavorable” in some variance. That unfavorable variance become production department responsibility.Keywords: responsibility accounting, production manager controlling, production manager assessment.